Funds management- acase study of hosdrug service co-operative bank LTD NO.1064 - Nitheesh B K (College of co-operation, banking and management, 2012)
The study entitled Funds Management - A case study of Hosdurg service co – operative bank was undertaken with the objective of analysing the existing funds management practice of HSCB Ltd. For studying the Funds Management 10 years audited data from 2000 – 01 to 2010 – 11 were employed. Ratio analysis was employed covering four categories viz. Ratio’s reflecting Efficiency in Mobilization and Deployment, Operational Officiency and Other Ratios reflecting the profitability was used for the study.